Catalogue of Tortricidae Latreille, 1802 (Lepidoptera: Tortricoidea) of India - Pathania, Prakash C.; Das, Apurva; Brown, John. W.; Chandra, Kailash (Zootaxa, 2020)
We present a catalogue of the species of Tortricidae Latreille, 1802 recorded from India. The documented fauna consists of 487 species belonging to 168 genera in three subfamilies: Chlidanotinae (14 species), Tortricinae (175 species), and Olethreutinae (298 species). Five species included in the catalogue were previously “named” but not properly described and are considered nomen nuda. We include these species because they are almost certainly distinct taxa and represent a part of the tortricid fauna. The catalogue is based primarily on literature in which Indian tortricid species have been described or mentioned. For each species the type locality, geographic distribution (within and outside of India), known host plants, and references to illustrations are provided.